Stabilization of Expansive Clay Soil with Fly Ash and Ground Granulated Blast Furnace Slag Materials on UCT Values (Case Study: Jalan Desa Sudimanik Kec.Sudimanik, Kab Pandeglang, Banten) - Kusuma, Rama Indera; Abdurrohim, Abdurrohim; Vihawian, Vini; Mina, Enden; Fathonah, Woelandari (Jurnal Fondasi, 2024)
Land is one of the important elements in construction projects and must have high bearing capacity to support the structure above it. Civil construction, whether roads, buildings, or other structures, will last a long time if one of the factors is supported by good subgrade. The location of the road in Sudimanik Village has soil that is classified as expansive clay, which has a high shrinkage capacity due to changes in water content. One way to improve unstable soil is to add additional materials such as Fly Ash and Ground Granulated Blast Furnace Slag (GGBFS).The purpose of this study was to determine the characteristics of the soil based on the classification and physical properties of the soil using the Unified Soil Classification System method and to determine the characteristics of the soil and the effect of adding consistent variations of fly ash at 20% and variations in the percentage of GGBFS 0%, 10%, 20%, and 30% as additional material for soil stabilization against the unconfined compressive strength value with variations in curing time of 0, 7, 14 and 28 days.The results of this study obtained soil classification according to the USCS classification including ML or inorganic silt and very fine sand, rock dust or fine silty or clayey sand. The plasticity index value after the study was 12.69%, in variation E, namely the addition of 20% fly ash and 30% GGBFS. The optimum qu value is in variation E with a curing time of 28 days, which is 2.287 kg / cm2. And experienced an increase in qu value of 295.918% from the original soil condition.